"Decision to Migrate" of Female Migrant Workers in Sendang Biru, Malang Regency - Keppi Sukesi; Henny Rosalinda; Yahya; Wahyu Handayani; Jedda Ayu Inggrida; Elok Anggraini; Rany Purnama Hadi; Rozaila Farcha (Salasika, 2022)
This paper aims to analyse the decision to migrate among the female villagers in a fishery village in East Java, Indonesia. Based on data from BP2MI, until November 2021, Malang Regency is a pocket for Indonesian female migrant workers. However, in Sendang Biru Hamlet, Tambakrejo Village, Sumbemanjing Wetan District, Malang Regency, East Java Province, only a few women choose to migrate. Using the mixed methods of quantitative and qualitative approaches, this study investigated the causes of international migration of women in the village. The quantitative data are derived from 204 household surveys while the qualitative data are analysed using the interview transcripts from semi-structured interviews with 21 current Indonesian female migrant workers and their left-behind families. The study has arrived at some interpretative points that the Sendang Biru Hamlet is a unique coastal area with specific community characteristics where women were given more access and opportunities in a productive public area by utilizing coastal resources as the main economic income. Therefore, migration is not the only favoured option for the female villagers to improve the living standard.